The Adoption of Smart Warehouse Technology in Thailand - Anatawat Chayutthanabun; Suthathip Suanmali; Thanwadee Chinda (Journal of Engineering, Project, and Production Management)
The growth of advanced technologies has been rising in recent years, which affects business operations throughout the supply chain. The smart warehouse is one of many technologies that increase warehouse management efficiency, for instance, increasing accuracy and reducing operating costs and processing times. Smart warehouse technologies are expected to be critical factors for effectively entering the fourth industrial revolution in Thailand. Currently, the utilization of smart warehouses in Thailand is not widespread; however, many organizations view such technologies as integral parts that will change the entire industry in Thailand. This research project explores and analyzes innovative warehouse technologies and their requirements for various industry sectors in Thailand. In addition, both qualitative and quantitative methods are employed to gather data. In-depth interviews of executives and warehouse managers are conducted, together with self-administered questionnaire surveys, to both smart warehouse users and providers. TOWS Analysis is applied to identify appropriate strategic options. Policy recommendations to effectively improve the unitization of smart and innovative warehouse technologies are also discussed.